1998
DOI: 10.1016/s0375-9474(98)00024-4
|View full text |Cite
|
Sign up to set email alerts
|

Photodisintegration of three- and four- nucleon systems

Abstract: Three- and four-nucleon photodisintegration processes are quite efficiently treated by means of effective two-body integral equations in momentum space. We recall some aspects of their derivation, present previous and most recent results obtained within this framework, and discuss general features, trends and effects observed in these investigations: At low energies final-state interaction plays an important role. Even more pronounced is the effect of meson exchange currents. A considerable potential dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 75 publications
3
21
0
Order By: Relevance
“…At the two lower energies the cross section maximum is decreased by adding the 3NF. A related effect has been seen before in [20] using different NN forces. Thereby it was found, that with increasing binding energy the value of the maximum decreased.…”
Section: Results For Pd (Nd) Photodisintegration Of 3 He ( 3 H)supporting
confidence: 75%
“…At the two lower energies the cross section maximum is decreased by adding the 3NF. A related effect has been seen before in [20] using different NN forces. Thereby it was found, that with increasing binding energy the value of the maximum decreased.…”
Section: Results For Pd (Nd) Photodisintegration Of 3 He ( 3 H)supporting
confidence: 75%
“…There is a small potential dependence of σ and, hence, of A 0 similar to the one observed in the corresponding photoprocess [13,14]. In view of the errorbars, the experimental data by Belt et al [1] and King et al [2,3] are reproduced for all potentials with the same quality.…”
supporting
confidence: 57%
“…In [13,14] we have shown that for different potentials the low-energy peak heights of the 3 He photodisintegration cross sections are strictly correlated with the corresponding 3 He binding energies, and with the number of partial waves included. The magnitude of the present radiative capture process, i.e., the constant A 0 , appears to be similarly fixed by the three-body binding energy.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, the Bonn group used the modern nucleon-nucleon forces. In these works, the current was restricted to the dominant E 1 multipole [6] or to the E 1 and E 2 multipoles [7]. They compared the Faddeev approach and a hyperspherical harmonic expansion together with the Lorentz integral transform method using AV18 together with Urbana IX.…”
Section: Introductionmentioning
confidence: 99%